THE CONSTRUCTION OF THE IDIOMS AND DEGREES OF OPACITY - Karimova Umida; Ashurova Shohista (American Journals Publishing, 2023)
This article gives information about the process of “idiomaticization” lies in diachronic evolution, idiomaticity cannot be adequately explained by the generative rules. Neither a given sense or a given syntactic structure by itself constitutes an idiom. Rather it is the regular association of one with the other that is the source of idiomaticity
Keywords: Authentic material, ESL classroom, context, teachable moment